A prospective study of screening for musculoskeletal pathology in the child with a limp or pseudoparalysis using erythrocyte sedimentation rate, C-reactive protein and MRI. (1st August 2018) - Mitchell, P. D.; Viswanath, A.; Obi, N.; Littlewood, A.; Latimer, M.
Abstract: Purpose: To determine if the detection of musculoskeletal pathology in children with a limp or acute limb disuse can be optimized by screening with blood tests for raised inflammatory markers, followed by MRI. Methods: This was a prospective observational study. Entry criteria were children (0 to 16 years of age) presenting to our emergency department with a non-traumatic limp or pseudoparalysis of a limb, and no abnormality on plain radiographs. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) blood tests were performed. Children with ESR > 10 mm/hr or CRP > 10 mg/L underwent a MRI scan. When the location of the pathology causing the limp was clinically unclear, screening images (Cor t1 and Short Tau Inversion Recovery) of both lower limbs from pelvis to ankles ('legogram') was undertaken. Data was gathered prospectively from 100 consecutive children meeting the study criteria. Results: In all, 75% of children had a positive finding on their MRI. A total of 64% of cases had an infective cause for their symptoms (osteomyelitis, septic arthritis, pyomyositis, fasciitis, cellulitis or discitis). A further 11% had positive findings on MRI from non-infective causes (juvenile idiopathic arthritis, cancer or undisplaced fracture). The remaining 25% had either a normal scan or effusion due to transient synovitis. ESR was a more sensitive marker than CRP in infection, since ESR was raised in 97%, but CRP in only 70%. Conclusion: In our opinion MRI imaging of all children with a limp and either raised ESR or CRP is a sensitive method to minimize the chance of missing important pathology in this group, and is an effective use of MRI resources. We advocate the use of both blood tests in conjunction. Level of Evidence: Level II